Cigarettes and Soviets : smoking in the USSR - Starks, Tricia, 1969- (NIU series in Slavic, East European, and Eurasian studies., 2022)
"Although the Soviets inaugurated the first national anti-smoking campaign, for reasons from countering popular discontent to exploiting mass addiction for revenue, production continued and increased. Following the story of Soviet tobacco through production, consumption, resistance, and support, this book complicates narratives of tobacco's rise based on western, capitalist markets"--